Boosting Hydrogen Evolution Reaction via Electronic Coupling of Cerium Phosphate with Molybdenum Phosphide Nanobelts. Issue 40 (7th September 2021) - Zhang, Luyao; Hu, Minghao; Li, Huan; Cao, Bo; Jing, Peng; Liu, Baocang; Gao, Rui; Zhang, Jun; Liu, Bin
Abstract: Molybdenum phosphide (MoP) is regarded as one of the most promising alternatives to noble‐metal based electrocatalysts for efficient hydrogen evolution reaction (HER) due to its similar d‐band electronic structure to noble metals and tunable features associated with phase and composition. However, it still remains a great challenge to construct MoP electrocatalysts with abundant active sites that possess ideal H binding strength to promote catalytic performance. In this work, it is found that by anchoring a rare earth compound, cerium phosphate (CePO4 ) on MoP (CePO4 /MoP), the stabilized Ce 3+ in CePO4 can significantly boost the formation of oxygen vacancies in ceria (CeO2 ) in situ formed on CePO4 surface during HER, which effectively regulates the d‐band electronic density‐of‐states of MoP, increases the numbers of active sites, and promotes the vectorial electron transfer, therefore greatly enhancing the HER performance of MoP. The optimized CePO4 /MoP/carbon cloth (CC) electrocatalyst exhibits a significantly improved HER performance with an overpotential of 48 mV at 10 mA cm −2 and a Tafel slope of 38 mV dec −1, about two times better than the HER performance of MoP catalyst without CePO4 (with an overpotential >80 mV dec −1 at 10 mA cm −2 ), very close to commercial Pt/C catalyst. Abstract : A heterostructured electrocatalyst of CePO4 /MoP/carbon cloth constituting MoP nanobelts with surface‐decorated CePO4 nanoparticles is constructed for hydrogen evolution reaction (HER). The Ce 3+ in CePO4 can promote the formation of oxygen vacancies in CeO2 formed on CePO4 surface during HER, which effectively regulates the electronic structure of MoP and increases the numbers of active sites, therefore greatly boosting the HER performance.